E-Filing, Kualitas Pelayanan, Sanksi Perpajakan dan Kepatuhan Wajib Pajak Orang Pribadi - Yuniasih, Ni Luh Putu Rika; Jati, I Ketut (E-Jurnal Akuntansi; Vol 31 No 12 (2021), 2021)
One of the effective methods and has great potential in increasing taxpayer compliance is tax reform. The purpose of this study was to determine the effect of the implementation of e-filing, the quality of tax services, and tax sanctions on the level of compliance of individual taxpayers. The population of this study is an individual taxpayer registered at the Tax Service Office (KPP) Pratama Denpasar Timur, amounting to 108,902 people. The sampling technique used is incidental sampling which takes 100 samples. Data was collected through the distribution of questionnaires. The analytical method used is Partial Least Square (PLS) Path Modeling with SmartPLS 3.0 analysis tool. The results of this study indicate that the higher the level of use in the application of e-filing, the higher the level of quality of tax services, and the more firm and fair in the application of tax sanctions, the higher the level of compliance of individual taxpayers. Keywords : E-Filing; Service quality; Tax Sanctions; Individual Taxpayer Compliance.